2022
DOI: 10.3390/pathogens11101102
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Discovery of a Competitive Inhibitor of FraB, a Salmonella Deglycase and Drug Target

Abstract: Although salmonellosis, an infectious disease, is a significant global healthcare burden, there are no Salmonella-specific vaccines or therapeutics for humans. Motivated by our finding that FraB, a Salmonella deglycase responsible for fructose-asparagine catabolism, is a viable drug target, we initiated experimental and computational efforts to identify inhibitors of FraB. To this end, our recent high-throughput screening initiative yielded almost exclusively uncompetitive inhibitors of FraB. In parallel with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The use of virtual screening methodologies to expedite the drug development timeline have gained momentum over recent years by substantially reducing the number of ligands that will need to be validated through experimental assays . Previously, our group and others have successfully implemented SBDD to identify small molecule binders for infectious and neurodegenerative diseases, cancer, heart failure, and various other acute conditions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual screening methodologies to expedite the drug development timeline have gained momentum over recent years by substantially reducing the number of ligands that will need to be validated through experimental assays . Previously, our group and others have successfully implemented SBDD to identify small molecule binders for infectious and neurodegenerative diseases, cancer, heart failure, and various other acute conditions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Although FrlB is the focus of this study, FraB, a related deglycase, has recently been identified as a novel drug target since disrupting the FraB‐dependent metabolism of F‐Asn by Salmonella results in the accumulation of a toxic sugar‐phosphate metabolite (Sabag‐Daigle et al, 2016). To this end, we have invested much effort to design a narrow‐spectrum therapeutic to inhibit Salmonella FraB (Sabag‐Daigle et al, 2023; Thirugnanasambantham et al, 2022). Our interest in FraB inspired our studies of the catalytic mechanism of Salmonella FrlB.…”
Section: Introductionmentioning
confidence: 99%